A study of BRAF mutation in colorectal carcinoma in Indian population - Saxena, Shilpi; Srinivas, V; Deb, Prabal; Raman, Deep; Jagani, Rajat (Journal of cancer research and therapeutics, 2018)
Context: BRAF mutation has been extensively studied and associated with various tumors. Targeted therapeutic intervention against BRAF mutation is established modality against many such tumors. Various studies have estimated that the prevalence of BRAF mutation in colorectal carcinoma (CRC) is 5%-25%. Considering epidemiology differences from Western population and paucity of studies on BRAF mutation in CRC in Asian patients, the present study was done to study the BRAF mutation in CRC in Indian population. Aims: The aim is to study the distribution of BRAF mutation and its correlation with the American Joint Committee on Cancer (AJCC) stage, grade, and other clinicopathological parameters in CRC. Settings and Design: This was a cross-sectional study. Subjects and Methods: Immunohistochemistry study was done using BRAFV600E monoclonal antibody (Clone VE1) for 65 consecutive cases of CRC in a tertiary care center. The results were statistically analyzed using SPSS version 2.0. Results: This study found that BRAF mutation is not significantly present in CRC as only 4.6% of cases were positive for BRAFV600E mutation. However, there was statistically significant relation between increasing AJCC stage and BRAF mutation. Conclusions: This study concluded that BRAF mutation is not prevalent in Indian population with CRC. However, it is significantly related with advanced AJCC stages.